The Lack of pedagogical contents aimed atteaching children english in the curriculum of Licenciatura en Idioma Inglés - Contreras Navarrete, Tania Leticia; Cubías Martínez, Silvia Cristina; González Henríquez, Telma Iris; Osorio Rebollo, Andrea Elizabeth; Rosa Cruz, Amalia Guadalupe; Carranza, Miguel Angel; Salazar Murcia, Pedro Antonio (Universidad de El Salvador, 2005)
The following essay is the result of the need of preparing students not only for teaching adults but also teaching children. Through our own experience, we have realized that we were not prepared to work with children in a formal way, which is different from teaching adults. Therefore, we see the need of including contents aimed at teaching children in the Licenciatura en Idioma Inglés so students can be more prepared at the time of teaching children. This paper will begin by first introducing a brief historical framework, in which the following aspects are mentioned: The beginnings of the teaching of English in El Salvador, the new programs that have been implemented by the Ministry of Education. Then theory about teaching children is presented and divided into: children`s behavior, techniques for teaching children and how children learn a second language. Next an analysis of the three Didactics programs is included; and another about teachers and students´ questionnaires. Finally a proposal is presented for the inclusion of a specific Didactics course aimed at teaching children, in the curriculum of the Licenciatura en Idioma Inglés.